Anomalous Doppler effect at interaction of electro-magnetic waves with electron beams: experimental researches and opportunities for application - Ivanov, B.I. (Вопросы атомной науки и техники, 2002)
The anomalous Doppler effect (ADE) in systems consisting of an electron beam and slow wave structure in longitudinal magnetic field is considered. Resonance condition for amplifiers and generators based on ADE enables resonance maintaining in case of wave phase velocity or beam velocity changing (acceleration of ions at ADE, reception of high efficiency at microwave generation). Essential advantages can be reached at combination of ADE and normal Doppler effect. The review of experimental studies of ADE is presented: amplification and generation of microwaves, energetic relations, excitation of accelerating IH-structures, development of ion acceleration.